HB Henderson's Boys : Eagle day - Muchamore, Robert (London : Hodder and Stoughton, 2017)
An airliner explodes over the Atlantic leaving 345 people dead. Crash investigators suspect terrorism, but they're getting nowhere. A distressed 12-year-old calls a police hotline and blames his father for the explosion. It could be a breakthrough, but there's no hard evidence.
Originally published in Great Britain in 2014 by Hodder Children's Books.
Ages 12 up.
Keywords: Spy stories, English; Spy stories, American